Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1747-0080.2010.01496.x
|View full text |Cite
|
Sign up to set email alerts
|

Student food insecurity: The skeleton in the university closet

Abstract: Aim:  Food security is an important nutrition issue among vulnerable population groups such as the young and socioeconomically disadvantaged. The present study sought to identify and describe the prevalence, distribution and severity of food insecurity, and related behavioural adaptations, among a sample of Australian university students. Methods:  A cross‐sectional survey design involving a self‐administered questionnaire consisting of 39 food security‐related and 15 demographic questions administered among a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
185
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(212 citation statements)
references
References 4 publications
17
185
3
Order By: Relevance
“…Previous research on food insecurity among college students has not asked respondents to report whether they were single parents (Chaparro et al, 2009;Hughes et al, 2011). National estimates of food insecurity have found that individuals who are raising children under the age of 18 without a spouse are more likely to experience food insecurity than the general population.…”
Section: Food Insecurity Prevalence and Demographicsmentioning
confidence: 96%
“…Previous research on food insecurity among college students has not asked respondents to report whether they were single parents (Chaparro et al, 2009;Hughes et al, 2011). National estimates of food insecurity have found that individuals who are raising children under the age of 18 without a spouse are more likely to experience food insecurity than the general population.…”
Section: Food Insecurity Prevalence and Demographicsmentioning
confidence: 96%
“…For example, food insecurity has been shown to be 1.5 times higher among Black and Hispanic students compared to White or Asian students. 17 Food insecure students were more likely to receive financial aid, 15 not live with family, 14, 18, 19 to have jobs while taking classes, 17, 19 and to have lower grades. 16 …”
Section: Introductionmentioning
confidence: 99%
“…16 This cross-sectional study found that food insecure students were more likely to report their health as being ‘fair’ or ‘poor.’ Studies from Australia have shown lower fruit and vegetable consumption among food insecure students 2 and null associations between weight status and food insecurity. 2, 19 Although it is likely that college students in other international settings may differ from those in the U.S., more research is needed in this area.…”
Section: Introductionmentioning
confidence: 99%
“…For example, food insecurity and domestic violence are of increasing concern at the student level (Hughes, Serebryanikova, Donaldson, & Leveritt, 2011;Rondeau, 2007). Education becomes a second order issue in relation to basic security needs.…”
Section: Securitymentioning
confidence: 99%